Juridical Review of The Wadas Village Dispute Based on The Law on Environmental Conservation And Management - Fina Nusa Puspa; Greha Wahyu Dayani; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2022)
The environment has an important role in human life because the environment supports the prosperity and welfare of human life both physically and mentally. Thus, development that has the potential to damage the environment can endanger human life not only in the present but also in the future, so it is important to maintain environmental sustainability. This study will try to describe how the right to a good and healthy environment is viewed from the provisions of Indonesian laws and regulations and whether andesite mining in Wadas Village has the potential to violate these constitutional rights. This research uses a normative juridical approach using secondary data in the form of library materials consisting of primary, secondary and tertiary legal materials. The results of this study indicate that the right to a good and healthy environment is a constitutional right of Indonesian citizens as outlined in the 1945 Constitution, the Law on Environmental Protection and Management and the MPR Decree No. XVII/MPR/1998 on Rights. Human Rights. Andesite mining in Wadas Village has the potential to damage the environment because the area is prone to landslides and is a water catchment area, so if the mining continues it can cause landslides and drought.